The Role of Heterotrimeric G-Protein Beta Subunits During Nodulation in Medicago truncatula Gaertn and Pisum sativum L. - Bovin, Andrey D.; Pavlova, Olga A.; Dolgikh, Aleksandra V.; Leppyanen, Irina V.; Dolgikh, Elena A. (Frontiers in Plant Science, 2022)
Heterotrimeric G-proteins regulate plant growth and development as master regulators of signaling pathways. In legumes with indeterminate nodules (e.g., Medicago truncatula and Pisum sativum), the role of heterotrimeric G-proteins in symbiosis development has not been investigated extensively. Here, the involvement of heterotrimeric G-proteins in M. truncatula and P. sativum nodulation was evaluated. A genome-based search for G-protein subunit-coding genes revealed that M. truncatula and P. sativum harbored only one gene each for encoding the canonical heterotrimeric G-protein beta subunits, MtG beta 1 and PsG beta 1, respectively. RNAi-based suppression of MtGbeta1 and PsGbeta1 significantly decreased the number of nodules formed, suggesting the involvement of G-protein beta subunits in symbiosis in both legumes. Analysis of composite M. truncatula plants carrying the pMtGbeta1:GUS construct showed β-glucuronidase (GUS) staining in developing nodule primordia and young nodules, consistent with data on the role of G-proteins in controlling organ development and cell proliferation. In mature nodules, GUS staining was the most intense in the meristem and invasion zone (II), while it was less prominent in the apical part of the nitrogen-fixing zone (III). Thus, MtG beta 1 may be involved in the maintenance of meristem development and regulation of the infection process during symbiosis. Protein–protein interaction studies using co-immunoprecipitation revealed the possible composition of G-protein complexes and interaction of G-protein subunits with phospholipase C (PLC), suggesting a cross-talk between G-protein- and PLC-mediated signaling pathways in these legumes. Our findings provide direct evidence regarding the role of MtG beta 1 and PsG beta 1 in symbiosis development regulation.